BUDIDAYA TANAMAN JAHE SELAKU PENGGERAK UTAMA USAHA MIKRO KECIL MENENGAH (UMKM) PADA INDUSTRI PERMEN DI RW 11, KELURAHAN CISARUA KECAMATAN CIKOLE KOTA SUKABUMI JAWA BARAT - Rahmawati, Anita; Fitria Azizah, Cica; Sutindi, Geri; Lenggani SM, Kinanti; Selvi Sri Rahayu, Neng (ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
Ginger is one of the herbal plants that can adapt well in Indonesian soil. This plant is timeless with various benefits and properties for the human body. Many processed foods and drinks are made from ginger, an example of its implementation is Ginger Candy. Ginger candy can be liked by various groups, ranging from children to adults. Candy can be a good medium for consuming this herbal plant. In Kelurahan Cisarua, many business people go into the business world with ginger candy as the main industry. However, most of them choose to order raw materials from outside the city instead of growing ginger independently. Polybag is one alternative to produce effective and efficient ginger raw materials, besides that it can also create jobs for the surrounding community to care for and cultivate ginger plants.